2021
DOI: 10.1536/ihj.20-458
|View full text |Cite
|
Sign up to set email alerts
|

Early Vascular Response to Ultrathin Biodegradable Polymer Sirolimus-Eluting Stents for the Treatment of ST-Elevation Myocardial Infarction After Plaque Rupture

Abstract: Recent clinical studies suggest that newer-generation drug-eluting stents that combine ultrathin struts and nanocoating (biodegradable polymer sirolimus-eluting stents, BP-SES) could improve long-term clinical outcomes in patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). However, the early vascular response to BP-SES in these patients has not been investigated so far.We examined this response in 20 patients with STEMI caused by plaque rupture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Miura et al 20 described the uncovered stent strut proportion of 7.7% at 2 weeks after O‐SES implantation, thus showing nearly complete endothelial coverage. Oishi et al 21 reported the uncovered stent strut proportion of 29.6% at 2 weeks after O‐SES in patients with ST‐elevation myocardial infarction, indicating NIC and the elimination of atheromatous plaques in the early phase after O‐SES implantation. Furthermore, Ogura et al 22 reported the uncovered strut proportion of 2.9% at 1 month after O‐SES implantation in patients with SAP, thus describing favorable NIC.…”
Section: Discussionmentioning
confidence: 99%
“…Miura et al 20 described the uncovered stent strut proportion of 7.7% at 2 weeks after O‐SES implantation, thus showing nearly complete endothelial coverage. Oishi et al 21 reported the uncovered stent strut proportion of 29.6% at 2 weeks after O‐SES in patients with ST‐elevation myocardial infarction, indicating NIC and the elimination of atheromatous plaques in the early phase after O‐SES implantation. Furthermore, Ogura et al 22 reported the uncovered strut proportion of 2.9% at 1 month after O‐SES implantation in patients with SAP, thus describing favorable NIC.…”
Section: Discussionmentioning
confidence: 99%